Eficácia do motile sperm organelle morphology examination (MSOME) na predição de gravidez após inseminação intrauterina - Akl, Lívia Drumond [UNESP] (2011)
Although motile sperm organelle morphology examination (MSOME) was developed only as a selection criterion, its application as a method for classifying sperm morphology may represent an improvement in the evaluation of semen quality. This study aimed to determine the prognostic value of normal sperm morphology by MSOME regarding clinical pregnancy (CP) after intrauterine insemination (IUI). A total of 156 IUI cycles performed in 111 couples were prospectively analyzed. All subjects received 75IU recombinant FSH every other day from the third day of the cycle. On the 10th day of the cycle, follicular development started to be monitored by vaginal ultrasound. When one or two follicles measuring ≥17mm were observed, recombinant hCG was administered and IUI was performed 12-14h and 36-40h after hCG. Before the IUI procedure, sperm samples were analyzed according to MSOME at 8400x magnification with an inverted microscope equipped with DIC/Nomarski differential interference contrast optics. At least 200 motile spermatozoa per semen sample were evaluated and percentages of normal spermatozoa were determined. Pregnancy occurred in 34 IUI cycles (CP rate per cycle: 21.8%, per patient: 30.6%). A statistically significant higher incidence of normal spermatozoa according to the MSOME criterion was found in the group of men in which IUI cycles resulted in pregnancy (2.6±3.1%) compared to the group that did not achieve pregnancy (1.2±1.7%; P=0.019). Logistic regression showed that the percentage of normal cells in the MSOME was determinant for the likelihood of clinical pregnancy (OR: 1.28; 95% CI: 1.08 to 1.51; P=0.003). The ROC curve showed an area under the curve of 0.63 and an optimum cut-off point of 2% of normal sperm form. At this cut-off level, the ability of the percentage of sperm normal form by MSOME to predict pregnancy present 50% sensitivity, 40% positive predictive value, 79%... (Complete abstract click electronic access below)